2004
DOI: 10.1523/jneurosci.2060-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Optical Postsynaptic Measurement of Vesicle Release Rates for Hippocampal Synapses Undergoing Asynchronous Release during Train Stimulation

Abstract: Developing hippocampal neurons in microisland culture were found to undergo rapid depression of excitatory synaptic activity caused by consumption of their readily releasable pool (RRP) of vesicles in response to 20 Hz trains of stimulation. Associated with depression was a switch to an asynchronous release mode that maintained transmission at a high steady-state rate equivalent to ϳ2.1 RRPs per second. We have applied postsynaptic Ca 2ϩ imaging to directly monitor these asynchronous release events to estimate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 55 publications
(81 reference statements)
5
14
0
Order By: Relevance
“…3B). Interestingly, the increment in asynchronous neurotransmission did not reduce synchronous release at any frequency of stimulation studied (QC at 20 and 40 Hz), as could be expected from previous studies (David and Barrett, 2003;Otsu and Murphy, 2004).…”
Section: Als-igg Enhances Asynchronous and Delayed Release At 20 And supporting
confidence: 84%
See 2 more Smart Citations
“…3B). Interestingly, the increment in asynchronous neurotransmission did not reduce synchronous release at any frequency of stimulation studied (QC at 20 and 40 Hz), as could be expected from previous studies (David and Barrett, 2003;Otsu and Murphy, 2004).…”
Section: Als-igg Enhances Asynchronous and Delayed Release At 20 And supporting
confidence: 84%
“…3D). Studies at neuromuscular and hippocampal synapses have shown that an increase in the asynchronous release reduces the synchronous release, probably because of the fact that vesicles involved in synchronous and asynchronous release derive from the same source (David and Barrett, 2003;Otsu and Murphy, 2004) (also see Sara et al, 2005).…”
Section: Als-igg Enhances Asynchronous and Delayed Release At 20 And mentioning
confidence: 99%
See 1 more Smart Citation
“…This notion was corroborated by the continuous release in those experiments of FM dye that had been preloaded into both the RRP and reserve vesicles. Indeed, high frequency electrical stimulation of hippocampal cells (a method normally used to trigger the RRP) leads to gradual mobilization of reserve vesicles (57).…”
Section: Discussionmentioning
confidence: 99%
“…The asynchronous release competes with synchronous release for the recovered quanta since they are derived from the same pool of readily releasable vesicles (Elmqvist and Quastel, 1965;Hagler and Goda, 2001;Lu and Trussell, 2000). As such, elevated asynchronous release can reduce future synchronous release (Otsu and Murphy, 2004). To test whether enhanced asynchronous release might be involved in the greater depression seen in APP −/− mice, we first measured asynchronous release by quantifying the frequency of minilike responses during a 10 min train at 30 Hz ( Figure 4).…”
Section: Increased Asynchronous Release Accompanied Greater Depressiomentioning
confidence: 99%